Synthesis and Characterization of Zeolite-Based Composites Functionalized with Nanoscale Zero-Valent Iron for Removing Arsenic in the Presence of Selenium from Water - Rubio-Campos, M; Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K; Sepúlveda-Ortiz, P; Sepúlveda-Ortiz, P (Elsevier B.V., 2019)
We studied the sorption of As(V) in single and multi-component (As(V)-Se(VI)) aqueous systems using nanoscale zero-valent iron (nZVI) and nZVI-functionalized zeolite (Z-nZVI) adsorbents. Morphological and physico-chemical characterization of the adsorbents was conducted using X-ray diffraction (XRD), scanning electron microscopy (SEM), surface area and electrophoretic mobility measurements. SEM and XRD analyses showed that Fe-nanoparticle size and crystallinity were better preserved in Z-nZVI than nZVI after As(V) sorption. Highly efficient As(V) removal was achieved for all tested adsorbents with a minimal competition effect of Se(VI). In the single-component system, the equilibrium As(V) sorption time on nZVI and Z-nZVI was 40 and 60 min, respectively, while in the multi-component system, this time was 90 min for both the adsorbents. The Freundlich and pseudo-second-order models provided good fittings for the experimental sorption data (r2>0.96). The As(V) removal capacity was higher using Z-nZVI than nZVI both in the single and multi-component systems, suffering minimal differences in removal in both cases. The results suggested that Z-nZVI had more specific surface sites for As(V) than nZVI and zeolite, which makes Z-nZVI a more effective adsorbent than nZVI for the removal of As(V) from aqueous solutions in the presence of other oxyanions. © 2019 Elsevier B.V.